(3ebGdI aj efGaY Gddjehfs - (3gHI Gddg Hf RjO Hf MSf Hf GaQGFje Hf jYbhH Hf LejY GdGSQGFjdj, GdeJWHH GdeUQj,J (B594 (3g` s
(3ChdgG (B:s
(3GdCN GdcQje hGdUOjb GdMeje ai JUQjajge Gddjehf ai cKjQ ef CZQGVge eY XghQ Ldjd efGaYg s
(3BNQgG (B:s
(3UaI Yed Nd Gddjehf jYSQ Gddjehf Ydi TF jSjQ ef GdedM HbOQ eG jMaXg ef GdJeQQ hGdMeO ddg Ydi eG CfYe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3bhHdJ gPg GdfSNI hUMMJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B72s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs